Wrist Flexibility and Service Accuracy in Table Tennis - Nasution, Usman; Ahady, Muhammad Yan; Sitanggang, Tama Rouli; Harahap, Ahlan Abadan; Tobing, Aditya Saputra Lumban; Aziz, Ridho Halim (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
The purpose of this research is to determine the improvement of basic wrist flexibility techniques with service accuracy. The research method used in this research is descriptive research. Descriptive research is research that attempts to describe a symptom, event, incident that is happening now. Serving ability is related to factors including flexibility of the wrist, the ball touched by the bet is swiped using arm and shoulder muscle strength, hand-eye coordination must be in line in placing the ball to the opponent, the speed of the ball must be different to make it difficult for the opponent to return the ball. , body balance, agility, and endurance.